Rekonstruksi Pendidikan Islam Berbasis Moderasi Beragama dalam Menguatkan Deradikalisasi Pasca Konflik Sosial di Kabupaten Poso - Ubaidillah Canu (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to reconstruct Islamic education based on religious moderation as an effort to strengthen deradicalisation in post-conflict society in Poso. This study employs a qualitative approach, emphasising the social experiences and religious practices of the community. Data were collected through in-depth interviews with religious leaders, educators and community members, as well as through observation of Islamic educational practices and daily religious life. The data analysis technique used is thematic analysis, conducted through the stages of data reduction, coding, theme grouping, interpretation of meaning, and drawing contextual conclusions. The results of the study indicate that religious moderation is understood in diverse ways, not merely as a normative concept, but also as the result of shared life experiences within socially vulnerable, conflict-prone situations. The reconstruction of Islamic education occurs not only in the curriculum but also in teaching methods and religious social practices. The values of tolerance (tasamuh), balance (tawazun), justice (i‘tidal), and moderation (wasathiyah) are internalised through daily social interactions. Deradicalisation in this context develops as a cultural process that unfolds gradually through dialogue and setting a good example. Although the region still faces challenges in the form of lingering conflict and exclusive religious views, there are local initiatives that are helping to strengthen social cohesion and build a more inclusive and sustainable community